Relevance of Sp binding site polymorphism in WWOX for treatment outcome in pancreatic cancer - Schirmer, Markus; Lüske, Claudia M.; Roppel, Sebastian; Schaudinn, Alexander; Zimmer, Christian; Pflüger, Ruben; Haubrock, Martin; Rapp, Jacobe; Güngör, Cenap; Bockhorn, Maximilian; Hackert, Thilo; Hank, Thomas; et al. (Journal of the National Cancer Institute, 2016)
A genome-wide association study (GWAS) suggested inherited genetic single-nucleotide polymorphisms (SNPs) affecting overall survival (OS) in advanced pancreatic cancer. To identify robust clinical biomarkers, we tested the strongest reported candidate loci in an independent patient cohort, assessed cellular drug sensitivity, and evaluated molecular effects.
Gesehen am 14.05.2020